Islamic Economic Empowerment for Al-Istiqomah Madrasah Santriwati in Karyomukti Village - Ririn Anggraeni; Dwi Wijayanti; Elsa Nisaha Rani; Hendri Hermawan Adinugraha; Happy Sista Devy (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
The implementation of this empowerment aims to add insight to Al-Istiqomah madrasah female students regarding the sharia economy that is related to the ethics of consumption in Islam. The implementation technique starts from coordination, determining participants, preparing the necessary tools, and evaluating activities. The method used in this empowerment is the lecture method using powerpoint media, and a question and answer session. It can be concluded from the results of this empowerment implementation that the majority of female students of madrasah al-istiqomah have not been able to apply consumption ethics in accordance with Islamic teachings, including by buying food or beverage products that have not been halal certified, buying goods that do not meet their needs (hedonism), and have not been able to identify haram and halal income.